Effect of Dried Mealworms (Tenebrio molitor), Larvae and Olive Leaves (Olea europaea L.) on Growth Performance, Carcass Yield and Some Blood Parameters of Japanese Quail (Coturnix coturnix japonica) - Ait-Kaki, Asma (Animals (Basel), 2021)
SIMPLE SUMMARY: Soybean is the most important protein source in poultry feed. Due to its high importation cost and its production arising generally from genetically modified organisms (GMOs), insects are currently considered to be a low-cost and eco-friendly alternative. In the present work, the inclusion of Tenebrio molitor (TM) insect meal and/or olive leaves (OL) in the basal quail diet has been tested on growth performance, carcass yield and some blood parameters. The results showed that 3% inclusion TM and 2% inclusion OL improved quail body weight at 5 weeks old, reduced FCR and did not negatively influence carcass yield and blood parameters of Japanese quail. In conclusion, the present work can contribute to a strategy aimed at reducing the use of conventional poultry feed ingredients, which might reduce the feeding costs of quails in Algeria. ABSTRACT: The aim of this study was to investigate the effect of Tenebrio molitor meal (TM) and/or olive leaf powder (OL) supplementation to quail diet on animal performance, carcass yield and some blood parameters. One hundred and forty-four 1-day-old Japanese quails (body weight: 29.9 ± 0.46 g) were divided into four groups of 36 chicks, receiving four different diets, i.e., G1: Standard commercial (SCD); G2: SCD + 3% TM; G3: SCD + 3% OL; and G4: SCD + 3% TM + 2% OL. Feed and water were provided ad-libitum. The results showed that TM and OL inclusion promoted quail body weight at 5 weeks of age; p = 0.001. Feed conversion ratio (FCR) of G3 was significantly (p < 0.01) reduced compared to the other groups. Overall mortality was not different, at around 6.25%, between groups. Carcass [(71.5–74.3%)], gizzard [(2.5–2.7%)], heart [(1.1–1.2%)] and giblet [(6.8–6.9%)] yields were not influenced by the diet. No significant effect of the diet was observed for serum proteins, creatinine, urea and lipids. To conclude, the mixture of an incorporation of TM and OL in quail diet showed no adverse effects on growth performance, carcass constituent yields and serum constituents.